Comparative genome‐wide methylation analysis of longissimus dorsi muscles in Yorkshire and Wannanhua pigs. (10th December 2020) - Li, X.‐J.; Liu, L.‐Q.; Dong, H.; Yang, J.‐J.; Wang, W.‐W.; Zhang, Q.; Wang, C.‐L.; Zhou, J.; Chen, H.‐Q.
Summary: DNA methylation was one of the earliest discovered epigenetic modifications in vertebrates, and is an important epigenetic mechanism involved in the expression of genes in many biological processes, including muscle growth and development. Its effects on economically important traits are evidenced in reported differences in meat quality traits between Chinese indigenous pig breeds (Wannanhua pig) and Western commercial pig breeds (Yorkshire pig), and this presents a unique model for analyzing the effects of DNA methylation on these traits. In the present study, a whole genome DNA methylation analysis was performed on the two breeds using methylated DNA immunoprecipitation. GO functional enrichment and pathway enrichment analyses identified differentially methylated genes primarily associated with fatty acid metabolism, biological processes of muscle development and signaling pathways related to muscle development and pork quality. Differentially methylated genes were verified by sodium pyrosequencing, and the results were consistent with the sequencing results. The results of the integrative analysis between DNA methylation and gene expression revealed that the DNA methylation levels showed a significantly negative correlation with gene expression levels around the transcription start site of genes. In total, 41 genes were both differentially expressed and methylated; these genes were related to fat metabolism, lipid metabolism and skeletal muscle development. This study could help further explore the molecular mechanisms and phenotypic differences in pig growth and development among different breeds.